An Islamic Pesrspective Of Superstitious Practices Related To Death Among Yoruba Muslims Of Ogun State - SURAJU Saheed Badmus; BADRUDEEN Musa Adebayo (MAQOLAT: Journal of Islamic Studies, 2025)
Superstition as a belief or tale is generally interesting to most people all over the world in general and the Yorubas in particular. It is a practice that cuts across all aspects of the human’s life; religion, social, moral, and economic. The Muslims’ involvement in these practices calls for attention of Muslim scholars and researchers. The Muslims in Ogun State are not excluded among the Yoruba Muslims from these practices. Thus, this paper aims at exposing the level of involvement of some Yoruba Muslims in the practice of khurāfāt (superstitions) related to death among other practices. The paper examines the Islamic perspectives of the practices with a view to determining their consonance or otherwise with the fundamental principles of Islam. So, through the use of historical, descriptive and analytical research methods; this paper accounts for the historical background of Ogun State; explains the superstition practices related to death in Ogun State and analyses the practices using the Qur’ān, Sunnah and views of the Islamic scholars. The research findings reveal that negligence of the Muslims is the foremost reason for the involvement in the practice as well as ignorance of the Islamic rules of funeral rites leading to giving preference to Yoruba cultural superstitious practices over Islamic practices. The paper, therefore, recommends that the Muslim leaders, parents, guardians, Islamic Studies teachers and religious organizations should pay adequate attention to Islamic faith-based teachings that are devoid of superstitious practices and other fetish beliefs in order to have well informed and reformed Muslims.